Peculiarities of the World Experience of State Financial Support of Innovations - ORYNBABASSAROVA, Yerkenazym; NABIYEV, Yerboz; LEGOSTAYEVA, Anna; KUTTYBAYEVA, Nurgul; KOPZHASSAROVA, Gaukhar; ASEL, Musynova (Journal of Advanced Research in Law and Economics, 2017)
The article examines the foreign practice of financial support for innovation activities of the two world powers of Great Britain and Japan, from each country experience is revealed that can be used in the domestic innovation system. Reflected tools to stimulate innovation in both countries, such as tax incentives, discounts and loans.